Specific and Nonspecific Cell-Mediated Resistance to Influenza Virus in Mice - Shayegani, Mehdi (1974)
We found that influenza virus had the capacity to replicate in the peritoneal macrophages of normal mice, as revealed by the development of hemadsorption and the appearance intracellularly of S and V antigens. Cell-mediated resistance was studied in mice infected with influenza virus or a bacterial sytem of induction-elicitation. In the homologous system, mice were injected intraperitoneally or exposed by aerosol to a sublethal dose of an egg-adapted swine strain of influenza virus. In the heterologous system, they were infected repeatedly with Staphylococcus aureus and elicited by subcutaneous or aerosol administration of staphylococcal antigens. The peritoneal macrophages from mice specifically or nonspecifically immunized were significantly more resistant than those from normal mice. Also longer survival to in vivo challenge by the mouse-adapted virus, as compared with normal mice, was indicated in bacterially stimulated mice.